Efficacy and Safety of Levetiracetam vs. Phenobarbital for Neonatal Seizures: A Systematic Review and Meta-Analysis - Qiao, Meng-Yuan; Cui, Hong-Tao; Zhao, Ling-Zhi; Miao, Jing-Kun; Chen, Qi-Xiong (Frontiers in Neurology, 2021)
Objective: To evaluate the efficacy and safety of levetiracetam (LEV) for neonatal seizure, and compare the efficacy, side effects, and neurological outcomes between LEV and phenobarbital (PB) in the treatment of neonatal seizure. Methods: The keywords of LEV、PB and neonatal seizure were searched in PubMed, MEDLINE, the Cochrane Library, wed of science, EMBASE, clinicaltrials.gov to collect high-quality studies. We collected studies studying the efficacy or safety of LEV and PB in the treatment of neonatal seizure from 1960 to 2021 years. Data were extracted through the strict inclusion and exclusion criteria. Outcome measures including efficacy, side effects rate, neurological score, mortality rate were performed by Revman 5.3 software. Results: Ten articles were finally included in the meta-analysis. Meta-analysis showed that there was no difference in efficacy between LEV and PB in the treatment of neonatal seizure (P=0.68). Compared with PB, the incidence rate of side effects of LEV was lower(P<0.0001). The incidence rate of hypotension and respiratory depression in LEV group was significantly lower than that in PB (P=0.001, P=0.04). In terms of long-term neurodevelopmental outcome, there was no significant difference in the Bayley Scales of Infant development (BSID) score of LEV and LEV (P=0.57, P=0.47). Conclusion: PB is still the first-line antiepileptic drugs (AEDs) recommended by WHO in the treatment of neonatal seizure. However, the new AEDs, LEV has good efficacy and high safety. The incidence of adverse effects of LEV is merely 0%-12%, and LEV has important value in the treatment of neonatal seizure.